Solar heating reflective coating layer (SHRCL) to cool the asphalt pavement surface. (15th May 2017) - Sha, Aimin; Liu, Zhuangzhuang; Tang, Kun; Li, Pinyi
Highlights: Solar heating reflective coating layer (SHRCL) was prepared to cool the asphalt pavement surface. Heating process downwards was measured and analyzed, and was divided into four stages. Durability of SHRCL was evaluated by Model Mobile Load Simulator. Abstract: The asphalt pavement heated by solar has attracted great attentions in heating urban cities, so-called urban heat island (UHI). In fact, the solar energy heating asphalt pavements also has potential ability to bring out geological disasters in permafrost, e.g., Qinghai-Tibet Plateau (QTP). This study designed a special solar heating reflective coating layer (SHRCL) in order to cool the asphalt pavement surface. The cooling performance of SHRCLs was studied by comparing the temperatures of normal pavements and SHRCLs. The result indicated that SHRCL could work as expected resulting in reducing around 10 °C compared to the normal pavement, no matter on the top or on the bottom. The temperature difference between the top and the bottom was about 5 °C, not only in SHRCLs but also in normal pavements, less linking with coating or un-coating. The field testing result agrees very well with the laboratory study. To enhance the skid resistance of SHRCLs, sands were added into coatings without influencing the cooling performance, but reducing the abrasive resistance. Accelerated pavement testing (APT) was employed to evaluate the engineering performance of SHRCL. It is suggested that inhomogeneous deformation, e.g., rutting, will bring cracking and spalling between asphalt pavement surfaces and coating layers.